Association Between METS-IR and Prehypertension or Hypertension Among Normoglycemia Subjects in Japan: A Retrospective Study - Han, Kai-Yue; Gu, Jianing; Wang, Zhangsheng; Liu, Jie; Zou, Su; Yang, Chen-Xi; Liu, Dan; Xu, Yingjia (Frontiers in Endocrinology, 2022)
Abstract Aim: Our study aimed to investigate the association between the novel non–insulin‐based metabolic score for insulin resistance (METS-IR) index and prehypertension or hypertension in normoglycemic participants in Japanese. Methods: This cross-sectional study was conducted between May 2004 and December 2005 in a Murakami Memorial Hospital in Gifu, Japan. From May 1st, 1994 to Dec 31st, 2016, 20,944 participants were enrolled in the medical examination program at Murakami Memorial Hospital in Japan to explore the association between the level of METS-IR index and prehypertension or hypertension. Covariates included demographic, clinical characteristics, serum biomarkers. Logistic regression was applied to explore the association between the level of METS-IR and prehypertension or hypertension. Results: A total of 15453 participants were included. The prevalence of prehypertension and hypertension was 28.55%(4412/15453) and 6.23%(962/15453), respectively. In the multivariate regression models, when METS-IR as a categorical variable, patients with higher METS-IR were significantly associated with prehypertension or hypertension (adjusted OR = 1.95, 95% CI: 1.61-2.36 and adjusted OR = 2.12, 95% CI: 1.44-3.11) after adjusting for confounding factors. Each 1 unit increase in METS-IR was associated with 7% increase in the prevalence of prehypertension (adjusted OR = 1.07, 95% CI: 1.06-1.08), and with 13% increase in the prevalence of hypertension (adjusted OR = 1.13, 95% CI: 1.10-1.16) when METS-IR as a continuous variable. The stratified analyses indicated that there was a positive correlation between METS-IR and prehypertension or hypertension in normoglycemic subjects with different characteristics. Conclusions METS-IR level is significantly associated with prehypertension or hypertension in normoglycemic participants in Gifu, Japan.